IMPLEMENTATION OF WORKING PROGRAMS IN EMPOWERMENT OF PRIVATE VOCATIONAL SCHOOL IN COMMUNITY INSTITUTION IN IIA SEMARANG - Khuswatun Chasanah; Zainal Hidayat (Journal of Public Policy and Management Review, 2019)
Norms become rules that must be regulated in social life, but today there are not a few people who violate the norm to point to criminal acts. Criminal offenders are referred to as convicts or prisoners who are serving sentences and coaching processes at the Correctional Institution. The correctional process must be carried out well, where in its implementation is an action taken by the government and the private sector both individually and in groups to achieve the objectives. The aim of this prison is to empower prisoners and with efforts to build power itself, by encouraging, motivating and raising awareness of their potential and trying to develop it. Correctional Institutions are technical units in implementing the Correctional System. Correctional based on the Decree of the Minister of Justice Number: M.02-PK.04.10 Year 1990 is an order regarding direction and boundary as well as a way of fostering for assisted citizens based on Pancasila which aims to awaken prisoners so that they do not go wrong, this is followed by Correctional Institutions Semarang Class IIA Women Regarding the Pattern of Guiding Prisoners or Prisoners which are divided into two namely Personality and Independence Development. This Personality Development focuses on trying to direct prisoners in thoughts, activities, and feelings that influence their behavior better. Self-Reliance Development focuses on skills programs to support independent businesses for the inmates characterized by the ability to form initiatives, create and innovate in carrying out skills programs in the field of work guidance, in the form of home industries, and managing raw materials into finished materials, and unused materials become valuable. In the coaching process it is influenced by factors such as: Human Resources, Coordination, Private Sector involvement and Communication which have a role in helping to create a good Correctional system in accordance with the Decree of the Ministry of Law and Human Rights.